Philippines : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
This 2011 Article IV Consultation reports that the Philippines is being affected along with other countries in the region by the fragile global environment. The key challenge is to navigate through the period of global uncertainty to maintain macroeconomic stability while building the foundations for faster and more inclusive growth. Domestic demand should support growth in 2012, as public spending picks up after a sharp decline in 2011, and IMF staff expects growth to rise from 3.7 percent in 2011 to 4.2 percent in 2012.